Children talking television: The salience and functions of media content in child peer interactions - Kampf, Zohar; Hamo, Michal (Discourse & Communication, 2015)
The study aims at exploring the salience and functions of media and television contents in children’s lives (aged 4–7 years) by focusing on their uses as a discursive resource in naturally occurring peer talk. We observed and recorded Israeli children talk in everyday, natural settings in two separate studies, in 1999–2002 and in 2012–2013. Detailed discourse analysis of television-based interactions from an ethnographic, child-centered perspective reveals the enduring centrality of television as an enjoyable, available, and shared cultural resource with valuable social, cognitive, and discursive affordances: it is frequently mentioned during everyday adult-free interactions; utilized as the basis for drawing and negotiating boundaries and hierarchies within the peer community; and facilitates experiencing a variety of discursive literacy skills, ranging between practicing adherence to original texts and creativity and distancing from them. These findings provide further evidence for the mediatization of everyday life, and may have educational implications, which are discussed.